Falsely Elevated 25-Hydroxy-Vitamin D Levels in Patients with Hypercalcemia - Moon Kyung Choi; Prapaipan Putthapiban; Patamaporn Lekprasert (Case Reports in Endocrinology)
Symptomatic hypercalcemia is a commonly encountered clinical scenario. Though it is important to collect detailed history to find clinical clues connecting to the etiology of hypercalcemia, the diagnostic workup of hypercalcemia depends heavily on laboratory analysis. Accurate measurement of the parathyroid hormone and vitamin D levels is essential. However, commercial laboratory measurement of vitamin D levels can be erroneous in the setting of abundant paraprotein in the serum. One of the most common conditions that can cause an increased amount of paraproteins is multiple myeloma. We report 2 cases of falsely elevated 25-hydroxy-vitamin D levels in patients presenting with hypercalcemia and an underlying diagnosis of MM.